An analytical approach to crowdinvesting: The impact of marketing and idea stealing on the entrepreneur's decision making - Nicola Bethmann; Matthias Frieden (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2019)
In a game theoretical setting, this paper studies the entrepreneur's decision making by using a new financing opportunity referred to as crowdinvesting. In this model, the entrepreneur can collect money and advertise his innovative idea. However, crowdinvesting carries the risk of being copied by a potential competitor. Faced with this trade-off, the entrepreneur strategically diminishes his marketing activity under certain circumstances to remain the monopolist in the market. In the second part, we compare crowdinvesting with two alternative financing opportunities, banks and venture capital. We show that crowdinvesting, often mentioned as a financing instrument for drastic innovations, is generally not appropriate for these ideas because the danger of being copied is too high for the entrepreneur.
Keywords: D21; G32; L26; M13; O13; 330; Crowdinvesting; equity crowdfunding; entrepreneurship; advertising; idea stealing